Obesity and Inflammation: Epidemiology, Risk Factors, and Markers of Inflammation - Heriberto Rodríguez-Hernández; Luis E. Simental-Mendía; Gabriela Rodríguez-Ramírez; Miguel A. Reyes-Romero (International Journal of Endocrinology)
Obesity is a public health problem that has reached epidemic proportions with an increasing worldwide prevalence. The global emergence of obesity increases the risk of developing chronic metabolic disorders. Thus, it is an economic issue that increased the costs of the comorbidities associated. Moreover, in recent years, it has been demonstrated that obesity is associated with chronic systemic inflammation, this status is conditioned by the innate immune system activation in adipose tissue that promotes an increase in the production and release of pro-inflammatory cytokines that contribute to the triggering of the systemic acute-phase response which is characterized by elevation of acute-phase protein levels. On this regard, low-grade chronic inflammation is a characteristic of various chronic diseases such as metabolic syndrome, cardiovascular disease, diabetes, hypertension, non-alcoholic fatty liver disease, and some cancers, among others, which are also characterized by obesity condition. Thus, a growing body of evidence supports the important role that is played by the inflammatory response in obesity condition and the pathogenesis of chronic diseases related.